Pharmacokinetics of articaine hydrochloride and its metabolite articainic acid after subcutaneous administration in red deer (Cervus elaphus). Issue 1 (2nd January 2018) - Venkatachalam, D; Chambers, JP; Kongara, K; Singh, P
Abstract : AIM: To develop and validate a simple and sensitive method using liquid chromatography-mass spectrometry (LC-MS) for quantification of articaine, and its major metabolite articainic acid, in plasma of red deer ( Cervus elaphus ), and to investigate the pharmacokinetics of articaine hydrochloride and articainic acid in red deer following S/C administration of articaine hydrochloride as a complete ring block around the antler pedicle. METHODS: The LC-MS method was validated by determining linearity, sensitivity, recovery, carry-over and repeatability. Articaine hydrochloride (40 mg/mL) was administered S/C to six healthy male red deer, at a dose of 1 mL/cm of pedicle circumference, as a complete ring block around the base of each antler. Blood samples were collected at various times over the following 12 hours. Concentrations in plasma of articaine and articainic acid were quantified using the validated LC-MS method. Pharmacokinetic parameters of articaine and articainic acid were estimated using non-compartmental analysis. RESULTS: Calibration curves were linear for both articaine and articainic acid. The limits of quantifications for articaine and articainic acid were 5 and 10 ng/mL, respectively. Extraction recoveries were >72% for articaine and >68% for articainic acid. After S/C administration as a ring block around the base of each antler, mean maximum concentrations in plasma ( C max ) of articaine were 1, 013.9 (SD 510.1) ng/mL, detected at 0.17 (SD 0.00) hours, and the C max for articainic acid was 762.6 (SD 95.4) ng/mL at 0.50 (SD 0.00) hours. The elimination half-lives of articaine hydrochloride and articainic acid were 1.12 (SD 0.17) and 0.90 (SD 0.07) hours, respectively. CONCLUSIONS AND CLINICAL RELEVANCE: The LC-MS method used for the quantification of articaine and its metabolite articainic acid in the plasma of red deer was simple, accurate and sensitive. Articaine hydrochloride was rapidly absorbed, hydrolysed to its inactive metabolite articainic acid, and eliminated following S/C administration as a ring block in red deer. These favourable pharmacokinetic properties suggest that articaine hydrochloride should be tested for efficacy as a local anaesthetic in red deer for removal of velvet antlers. Further studies to evaluate the safety and residues of articaine hydrochloride and articainic acid are required before articaine can be recommended for use as a local anaesthetic for this purpose.